Nirsevimab: a change of paradigm in the prophylaxis of Respiratory Syncytial Virus disease among infants - Rezza, Giovanni; Cereda, Danilo; Rizzo, Caterina; Cuciniello, Rita; Carole D'Amelio, Anna; Villani, Alberto; Signorelli, Carlo (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
.